An enzyme-controlled mesoporous nanomachine for triple-responsive delivery. Issue 36 (25th August 2022) - Mayol, Beatriz; Dato, Victor; Rodriguez, Manuel; Lucena, Elena; Villalonga, Anabel; Díez, Paula; Jimenez-Falcao, Sandra; Sancenón, Félix; Sánchez, Alfredo; Vilela, Diana; Martínez-Ruiz, Paloma; Martínez-Máñez, Ramón; et al.
Abstract : The construction of a novel enzyme-controlled nanomachine with multiple release mechanisms for on-command delivery is described. Abstract : The construction of a novel enzyme-controlled nanomachine with multiple release mechanisms for on-command delivery is described. This nanodevice was assembled by modifying mesoporous silica nanoparticles with 2-(benzo[ d ]thiazol-2-yl)phenyl 4-aminobenzoate moieties, and further capped with β-cyclodextrin-modified glucose oxidase neoglycoenzyme. The device released the encapsulated payload in the presence of H2 O2 and acidic media. The use of glucose as an input chemical signal also triggered cargo release through the enzymatic production of gluconic acid and hydrogen peroxide, and the subsequent disruption of the gating mechanism at the mesoporous surface. The nanodevice was successfully employed for the enzyme-controlled release of doxorubicin in HeLa cancer cells.